Pemanfaatan Urine Domba dalam Pembuatan Pupuk Organik Cair dan Pestisida Nabati - Rendi Irawan; Asroh Asroh; Kumala Intansari; Nanda Delvia Meisani; Titin Patimah; Afton Atabany (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
Sukamaju Village is one of the villages in Serang Regency which has the potential for sheep farming under the assistance of the Serang Regency Agriculture Service. Management of the sheep business in this target group is generally still inadequate, where solid and liquid waste has not been properly managed. Farmers do not know the technicalities of waste management well. The urine produced by sheep is only stored in a container without being used to become something that is more beneficial and environmentally friendly. Even though the sheep urine can be processed into liquid organic fertilizers and vegetable pesticides. This research was conducted on 13 August - 20 August 2020 at the sheep breeder's house in Sukamaju Village, Cikeusal District, Serang Regency, Banten Province. The materials used in this research are sheep urine as the basic ingredient for making liquid fertilizer (biourin), Effective microorganism 4 (EM4) and empon-empon which includes galangal, betel leaf, ginger, turmeric, and shrimp paste. Meanwhile, the tools used are water vats, stirrers, and liquid fertilizer containers. The results obtained from the process of making liquid organic fertilizers and vegetable pesticides from sheep urine are the color of the liquid fertilizer after the fermentation process is blackish brown and smells good. The results of making this liquid fertilizer after being given to plants can be seen that the plants are getting fresher and there are no harmful microorganisms (pests) around the plant. This proves that liquid fertilizers and vegetable pesticides work well. The response of the breeders was happy when this liquid organic fertilizer was successfully applied to their farms. Furthermore, the process of making liquid organic fertilizers and natural pesticides will be continued independently by farmers in Sukamaju Village, Cikeusal District, Serang Regency, Banten Province. Keywords: Empon-empon, vegetable pesticides, liquid organic fertilizer, sheep urine